Suppression of segregation and control of the structure of ingots and casting - Shapovalov, V.O.; Grigorenko, G.M.; Nikitenko, Yu.O.; Yakusha, V.V.; Shapovalov, E.V. (Вопросы атомной науки и техники, 2020)
The problem of segregation in large ingots, which are used in energy, heavy engineering, etc., is considered. A new approach to suppressing segregation processes is proposed. It consists in regulating the local crystallization time by organizing a surfaced local metal bath on the surface and adjusting the speed of its movement, while an ingot is formed layer by layer.